Successful intravenous thrombolysis of a wake-up stroke with underlying valvular atrial fibrillation - Koya Kutty, Shahedah; Ching, Soong Khoo; Wan Yahya, Wan Nur Nafisah; Ng, Chen Fei; Md Sari, Noor Ashikin; Mohd Yaakob, Mohd Naim; Osman, Syazarina Sharis; Zakaria, Rozman; Wan Zaidi, Wan Asyraf (Royal College of Physicians of Edinburgh, 2018)
A 42-year-old female admitted with new-onset atrial fibrillation had a wake-up stroke on the high-dependency unit and the time last seen well (TLSW) was 6.5 h. She suffered left-sided body weakness and her National Institutes of Health Stroke Scale (NIHSS) score was 17. An emergency CT perfusion showed right M1 segment occlusion with more than 50% penumbra. She was given recombinant tissue plasminogen activator (r-tPA) at 9 h from TLSW. An immediate diagnostic angiogram with intention to treat, owing to the presence of large vessel occlusion, showed complete reperfusion after intravenous r-tPA. She was discharged with NIHSS of 2, and at 3-month follow up her Modified Rankin Scale was 0. We demonstrated a successful reperfusion and excellent clinical recovery with intravenous thrombolysis in a patient who presented with a wake-up stroke with underlying valvular atrial fibrillation despite evidence of large vessel occlusion. © 2018, Royal College of Physicians of Edinburgh. All rights reserved.